2016
DOI: 10.18632/oncotarget.8495
|View full text |Cite
|
Sign up to set email alerts
|

Storkhead box 2 and melanoma inhibitory activity promote oral squamous cell carcinoma progression

Abstract: BackgroundStorkhead box protein 2 (STOX2) is a transcriptional factor associated with pre-eclampsia with fetal growth restriction. We recently reported that melanoma inhibitory activity (MIA) promotes oral squamous cell carcinoma (OSCC) progression. However, the relationship between STOX2 and MIA remains unknown in malignancies.MethodsWe used immunohistochemistry and PCR to investigate MIA and STOX2 expression in OSCC. We also performed functional analysis in human OSCC cells.ResultsMIA and STOX2 mRNA levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…The gene expression levels of MIA were higher in the OSCC samples than in the normal oral mucosa . The expression of MIA was also higher in the invasive OSCC than in the carcinoma in situ .…”
Section: Otormentioning
confidence: 81%
See 4 more Smart Citations
“…The gene expression levels of MIA were higher in the OSCC samples than in the normal oral mucosa . The expression of MIA was also higher in the invasive OSCC than in the carcinoma in situ .…”
Section: Otormentioning
confidence: 81%
“…We previously reported that the melanoma inhibitory activity ( MIA ) gene family is involved in the tumor progression of OSCC . The members of the MIA gene family are secreted proteins that comprise MIA, MIA2, transport and Golgi organization protein 1 (TANGO or MIA3), and otoraplin (OTOR or fibrocyte‐derived protein and MIA‐like) .…”
Section: Melanoma Inhibitory Activity Gene Familymentioning
confidence: 99%
See 3 more Smart Citations